2003
DOI: 10.1093/emboj/cdg494
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and snapshots along the reaction pathway of a family 51  -L-arabinofuranosidase

Abstract: contributed equally to this work High-resolution crystal structures of a-L-arabinofuranosidase from Geobacillus stearothermophilus T-6, a family 51 glycosidase, are described. The enzyme is a hexamer, and each monomer is organized into two domains: a (b/a) 8 -barrel and a 12-stranded b sandwich with jelly-roll topology. The structures of the Michaelis complexes with natural and synthetic substrates, and of the transient covalent arabinofuranosyl± enzyme intermediate represent two stable states in the double di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 57 publications
(76 reference statements)
9
128
0
10
Order By: Relevance
“…If so, the conformation is the same as that of the Michaelis complex with arabinofuranose-␣ (1, 3)-xylopyranose reported for GH51 GsAbfA (Fig. 5B) (15). However, the limited crystallographic resolution does not allow detailed discussion of the sugar conformation of AkAbfB.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…If so, the conformation is the same as that of the Michaelis complex with arabinofuranose-␣ (1, 3)-xylopyranose reported for GH51 GsAbfA (Fig. 5B) (15). However, the limited crystallographic resolution does not allow detailed discussion of the sugar conformation of AkAbfB.…”
Section: Resultsmentioning
confidence: 53%
“…The distances between these sulfur atoms and the C-4/C-5 atoms of arabinofuranose are about 4 Å, and this disulfide bond seems to recognize these carbon atoms through hydrophobic interaction. In GH51 GsAbfA, a tryptophan side chain replaces this disulfide bond and similarly recognizes the carbon atoms of arabinofuranose through hydrophobic interaction (15). A disulfide bond between adjacent cysteines joined by a cis-peptide bond has been rarely reported, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a, c and e). Although the higher-order oligomeric form detected for both enzymes has an estimated molecular mass close to the pentamer, two lines of evidence suggest that this form corresponds to a hexamer: (i) the crystal structures of AbfA from G. stearothermophilus and Araf51 from C. thermocellum, which display 71 % and 63 % identity, respectively, to AbfA from B. subtilis, showed that they are organized as hexamers, trimers of dimers (Hovel et al, 2003;Taylor et al, 2006); (ii) the cross-linking experiments did not reveal a trimeric form, favouring the oligomerization as dimers and a higher-order structure with a mass greater than 250 kDa.…”
Section: Localization Of Abfa and Abf2 Activitiesmentioning
confidence: 99%